The Influence Of Product Development Strategy, Marketing Capability, and Institutional Support On Export Performance: Study on Coffee SMEs that are Members of the Pasuruan Kapiten Organization - Wibowo, Nyuherno Aris; Sudarmiatin; Handayati, Puji (International Humanity Advance, Business & Sciences, 2025)
This study aims to analyze the influence of product development strategy, marketing capability, and institutional support on export performance in coffee MSMEs that are members of the Kapiten Pasuruan organization. This study uses a quantitative approach with data collection techniques using a Likert scale questionnaire distributed to 30 MSMEs members of Kapiten Pasuruan. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach. The results of the study indicate that product development strategy has a positive and significant effect on export performance with a path coefficient of 0.437 (t-value = 3.842). Marketing capability has a positive and significant effect with a path coefficient of 0.365 (t-value = 3.251). Institutional support also has a positive and significant effect with a path coefficient of 0.298 (t-value = 2.975). These findings indicate that coffee MSMEs that are able to develop innovative product strategies, improve marketing capabilities, and optimally utilize institutional support have a greater opportunity to improve their export performance. The study suggests the need to strengthen product innovation capacity, develop international marketing competencies, and optimize institutional support to increase the competitiveness of Indonesian coffee MSMEs in the global market.